Cytotaxonomy of Four Species of the Genus Heliotropium L. (Boraginaceae) from the State of Punjab, India - Singh, Rai (Indian Forester, 2023)
Four Heliotropium species viz. H. bacciferum, H. currasavicum, H. ellipticum and H. strigosum were collected from different kharif crops in Malwa region of Punjab, India during the years 2019-2021. Various morphological features were analyzed for identification of species. Chromosome numbers were also studied for establishment of identity of species. Chromosome number varies from 2n=32 to 2n= 64.